Tip dependence of three-dimensional scanning force microscopy images of calcite–water interfaces investigated by simulation and experiments. Issue 24 (10th June 2020) - Miyazawa, Keisuke; Tracey, John; Reischl, Bernhard; Spijker, Peter; Foster, Adam S.; Rohl, Andrew L.; Fukuma, Takeshi
Abstract : In this study, we have investigated the influence of the tip on the three-dimensional scanning force microscopy (3D-SFM) images of calcite–water interfaces by experiments and simulations. Abstract : In this study, we have investigated the influence of the tip on the three-dimensional scanning force microscopy (3D-SFM) images of calcite–water interfaces by experiments and simulations. We calculated 3D force images by simulations with the solvent tip approximation (STA), Ca, CO3 and OH tip models. For all the 3D images, the z profiles at the surface Ca and CO3 sites alternately show oscillatory peaks corresponding to the hydration layers. However, the peak heights and spacings become larger when the mechanical stability of the tip becomes higher. For analyzing the xy slices of the 3D force images, we developed the extended STA (E-STA) model which allowed us to reveal the strong correlation between the hydration structure just under the tip and the atomic-scale force contrasts. Based on these understandings on the image features showing the strong tip dependence, we developed a method for objectively estimating the similarity between 3D force images. With this method, we compared the simulated images with the three experimentally obtained ones. Among them, two images showed a relatively high similarity with the image obtained by the simulation with the Ca or the CO3 tip model. Based on these agreements, we characterized the hydration structure and mechanical stability of the experimentally used tips. The understanding and methodology presented here should help us to derive accurate information on the tip and the interfacial structure from experimentally obtained 3D-SFM images.